Hydrogel viscoelasticity modulates migration and fusion of mesenchymal stem cell spheroids - David T. Wu; Mani Diba; Stephanie Yang; Benjamin R. Freedman; Alberto Elosegui‐Artola; David J. Mooney (Wiley, 2023)
Abstract Multicellular spheroids made of stem cells can act as building blocks that fuse to capture complex aspects of native in vivo environments, but the effect of hydrogel viscoelasticity on cell migration from spheroids and their fusion remains largely unknown. Here, we investigated the effect of viscoelasticity on migration and fusion behavior of mesenchymal stem cell (MSC) spheroids using hydrogels with a similar elasticity but different stress relaxation profiles. Fast relaxing (FR) matrices were found to be significantly more permissive to cell migration and consequent fusion of MSC spheroids. Mechanistically, inhibition of ROCK and Rac1 pathways prevented cell migration. Moreover, the combination of biophysical and biochemical cues provided by fast relaxing hydrogels and platelet‐derived growth factor (PDGF) supplementation, respectively, resulted in a synergistic enhancement of migration and fusion. Overall, these findings emphasize the important role of matrix viscoelasticity in tissue engineering and regenerative medicine strategies based on spheroids.